A grid enabled E-theses and dissertations repository system - Por, L.Y.; Ong, S.Y.; Beh, D.; Ismail, M. (2002)
Some of the universities in Malaysia are still implementing hybrid Electronic Theses and Dissertations (ETD) approach in managing Theses and Dissertations (TD). One of the limitations of the hybrid ETD approach is its online cataloguing method, which is only available at the physical location of the TD instead of enabling the information to be retrieved online. Maintaining the performance and the data accessing rate of an ETD system has become challenging, due in part to the high number of scholars who utilise and access the system. In order to allow remote access and maintain the services such as scalability, accessibility, availability and expressibility, a Grid Enabled E-Theses and dissertations repository system (GREET) has been proposed in this paper to provide uniform access of knowledge integration among distributed heterogeneous platforms and repositories by using data grid technology. Comparative performance results between a non-grid architecture and GREET has been benchmarked. It has been proven that GREET is able to increase the processing time approximately three times faster than the non-grid architecture. Furthermore, multiple file streams can be opened to support larger volume and larger capacity of file operation so that GREET is able to decrease the chances of network congestion caused by input/output file operations. For future direction, research will be focused on searching algorithm using data mining or pattern discovery to minimise the respond time.